THE INFLUENCE OF DIGITAL MARKETING, PROMOTION, AND SERVICE QUALITY ON CUSTOMER REPURCHASE INTENTION AT HUB22 LOUNGE & BISTRO SURABAYA - Florensia Vivin Ardisa; J.E. Sutanto; Michael Ricky Sondak (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The study entitled “The Influence of Digital Marketing, Promotion, and Service Quality on Customer Repurchase Intention at Hub22 Lounge & Bistro Surabaya” has four objectives, namely: (1) Knowing the effect of digital marketing on repurchase intention partially, (2) Knowing the effect of promotion on repurchase intention partially, (3) Knowing the effect of service quality on repurchase intention partially, (4) Knowing the effect of digital marketing, promotion, service quality on repurchase intention simultaneously. Hub22 Lounge & Bistro Surabaya is a business engaged in food and beverages. This research uses quantitative methods. The population in this study was the customers of Hub22 Lounge & Bistro who made transactions for the last six months. The sample in this study amounted to 140 respondents. Data collected through the distribution of questionnaires were distributed online using SPSS version 26. The results of this study are: (1) Digital Marketing partially has a significant effect on repurchase intention, (2) Promotion partially has a significant effect on repurchase intention, (3) Service quality partially has a significant effect on repurchase intention, and (4) Digital marketing, promotion, service quality simultaneously have a significant effect on repurchase intention.